2015
DOI: 10.1007/s00265-015-1942-9
|View full text |Cite
|
Sign up to set email alerts
|

Social living without kin discrimination: experimental evidence from a communally breeding bird

Abstract: In many cooperative animal societies, individuals can recognize their relatives and preferentially direct helping behaviors towards them. However, the ability to learn kin recognition cues may be constrained in societies with low relatedness, since group membership alone is not a reliable proxy for kinship. Here, we examine kin discrimination in the greater ani (Crotophaga major), a communally nesting bird in which several unrelated males and females reproduce in a single, shared nest and provide parental care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…If instead males are responding to the strategies of females, then the amount of care provided by males could be in response to a perceived idea of how many chicks in a brood they have sired [ 56 58 ], even if feeding efforts increase when the female has mated with more than one male [ 59 , 60 ]. Different studies have suggested that males (of the study species) cannot recognize, or at least do not discriminate against, unrelated chicks [ 61 , 62 ], so we can’t determine which hypothesis best explains the observed relationship; the results simply provide strong evidence that rates of EPP are related to male care. One potential issue is that there may be bias—out of 18 species for which data were available, only two lacked any form of mate guarding ( Vireo solitarius and Agelaius phoenicus , [ 52 , 63 , 64 ]).…”
Section: Discussionmentioning
confidence: 98%
“…If instead males are responding to the strategies of females, then the amount of care provided by males could be in response to a perceived idea of how many chicks in a brood they have sired [ 56 58 ], even if feeding efforts increase when the female has mated with more than one male [ 59 , 60 ]. Different studies have suggested that males (of the study species) cannot recognize, or at least do not discriminate against, unrelated chicks [ 61 , 62 ], so we can’t determine which hypothesis best explains the observed relationship; the results simply provide strong evidence that rates of EPP are related to male care. One potential issue is that there may be bias—out of 18 species for which data were available, only two lacked any form of mate guarding ( Vireo solitarius and Agelaius phoenicus , [ 52 , 63 , 64 ]).…”
Section: Discussionmentioning
confidence: 98%
“…In this article, I first show that infanticide is a significant cause of nestling mortality, and I present evidence that at least some infanticides are committed by reproductively active group members who were potential parents of the victims. This was surprising since previous cross‐fostering experiments have suggested that adult Greater Anis are incapable of recognizing their own offspring in the communal clutch, indicating that killers are unlikely to be able to selectively discriminate against unrelated nestlings based on recognition alone (Riehl and Strong ). I therefore test the hypothesis that the occurrence of infanticide may instead be related to the timing of reproduction by adults in the communal group; specifically, that early‐hatched nestlings are at greater risk of being killed.…”
mentioning
confidence: 95%
“…In species where several reproducing females indiscriminately care for offspring in a joint nest, females share costs equally, but the benefits for the individuals can vary depending on the number of offspring they have in the nest and the amount of care they provide. Indiscriminate care of young has been described for a number of communally breeding species such as beetles [15], birds [16], bats [17] and rodents [18]. Communal offspring care may also be conditional, because individuals can choose to participate in the public good (by forming a communal nest) [19][20][21] or nest solitarily instead.…”
Section: Introductionmentioning
confidence: 99%